PENGARUH LATIHAN ZIG-ZAG RUN TERHADAP KETERAMPILAN TENDANGAN SABIT EKSTRAKURIKULER PENCAK SILAT MAN 2 CIANJUR - Adella Gigis Adirgadira Sundawa; Ayui Irawan, Astri; Susianti, Evi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to evaluate and analyze the effect of zig-zag run training on theskills of Sisawa's crescent kicks in extracurricular pencak silat activities at MAN 2Cianjur. The research method used is experimentation with a quantitativeapproach. The research population consisted of 20 students who were membersof the pencak silat extracurricular, who were taken using total samplingtechniques. This research design uses a pre-experiment with a one-group pretestposttestmodel. The instrument used for data collection was the sickle kick skilltest. The data obtained was analyzed using SPSS 26 for Windows. The researchresults showed a significant increase in students' sickle kicking skills, with a meanpretest score of 66.60 and a mean posttest score of 76.85. Hypothesis testingusing a paired sample T test gives a significance value (2-tailed) of 0.000 which issmaller than 0.05, indicating that there is a significant influence between thevalues before and after treatment. Thus, it can be concluded that zig-zag runtraining has a positive influence on sickle kick skills in pencak silat extracurricularactivities at MAN 2 Cianjur.